European position statement on lung cancer screening. Issue 12 (December 2017) - Oudkerk, Matthijs; Devaraj, Anand; Vliegenthart, Rozemarijn; Henzler, Thomas; Prosch, Helmut; Heussel, Claus P; Bastarrika, Gorka; Sverzellati, Nicola; Mascalchi, Mario; Delorme, Stefan; Baldwin, David R; Callister, Matthew E; et al.
Summary: Lung cancer screening with low-dose CT can save lives. This European Union (EU) position statement presents the available evidence and the major issues that need to be addressed to ensure the successful implementation of low-dose CT lung cancer screening in Europe. This statement identified specific actions required by the European lung cancer screening community to adopt before the implementation of low-dose CT lung cancer screening. This position statement recommends the following actions: a risk stratification approach should be used for future lung cancer low-dose CT programmes; that individuals who enter screening programmes should be provided with information on the benefits and harms of screening, and smoking cessation should be offered to all current smokers; that management of detected solid nodules should use semi-automatically measured volume and volume-doubling time; that national quality assurance boards should be set up to oversee technical standards; that a lung nodule management pathway should be established and incorporated into clinical practice with a tailored screening approach; that non-calcified baseline lung nodules greater than 300 mm 3, and new lung nodules greater than 200 mm 3, should be managed in multidisciplinary teams according to this EU position statement recommendations to ensure that patients receive the most appropriate treatment; and planning for implementation of low-dose CT screening should start throughout Europe as soon as possible. European countries need to set a timeline for implementing lung cancer screening.